Analisis Faktor-Faktor yang Mempengaruhi Service Excellence (Studi Kasus pada PT. Bank X (Persero), Tbk. Pekanbaru) - Abdul Jalal (Bahtera Inovasi, 2019)
Service excellence is become an important thing for banking in Indonesia. This research analyzes factors influencing service excellence in PT. Bank X (persero), Tbk. Pekanbaru. The research problem is how to increase service excellence. This research builds a model and three hypotheses to answer the research problem. Respondents of this research are 102 persons. Respondents are staff of Bank X. This research uses Statistical Package for Social Science (SPSS) 17.0 program as analysis tools. The data analysis result of this research shows that research model and result can be accepted. The result of the research proves that interaction between departements, marketing information system and control system have positive and significant influence to service excellence. The higher interaction between departements, marketing information system and control system, the higher service excellence. Based on the results of the research could be taken theoretical implications that this research gives more justification for antecedents positively influence service excellence, i.e.: interaction between departements, marketing information system and control system. Managerial implications of this research are Bank X management need to pay attention to activity evaluation and it feed back, Bank X management need to always upgrade hardware and software marketing information system, and bank x management need to increase communication between departments so that service excellence is always expected to realized. Based on the limitation, agenda for future research are adding other variables influencing service excellence and repairing sampling method